(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
According to SOLAS, it is mandatory to provide all sailing vessels with an efficient main steering gear as well as an auxiliary steering gear. For turning the ship to the left (port side) or to the right (starboard side), while sailing, the steering gear is used. The requirement is that the main steering gear should be power operated except in the case of very small vessels/ships. The steering gear control system is the equipment by which helm orders/autopilot orders are transferred from the wheelhouse to the power units of the steering gear. The Steering Gear control system consists of the electrical wiring, electrical motors, hydraulic pumps, piping, receivers, transmitters, and control equipment. This paper focuses on relay based Robot for automated isolating Systems used in Steering Gear of a Ship and the comparison of the performance of a manual isolating system and Automatic Isolating system with robotic relay logic control. An experimental hardware prototype is designed and developed to compare the performance of steering gear isolating systems. The developed hardware is tested successfully and found that, it is better with respect to the following features. • Fault Isolation time. • Independent operation. • Operation of steering gear in various healthy and faulty conditions.